Studi Literatur: Analisis Penerapan Teknologi dalam Pembentukan Karakter Siswa - Sarmila Fitri Yanti Nasution; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Engineering is a science that studies the skills of creating tools and processing methods to perform various human tasks. Education is the conscious effort to prepare students for future tasks through teaching, learning and/or training. Character is a set of qualities that are always admired as a sign of a person's goodness, virtue and moral maturity. The purpose of this research is to conduct a literature review, ie. to find out the importance of technology in the development of a student's character. The method used is the Systematic Literature Review (SLR) strategy. SLR is a research method that aims to systematically identify, examine and interpret information obtained from journals at certain stages. The research results show that the integration of technology into education not only supports the learning process, but also plays an important role in the development of the student's character. Technology-based education encourages students to think critically, collaborate and adapt to the rapid changes of the digital age. Therefore, technology is an important tool to develop students who are academically intelligent in accordance with the values of Pancasila, but also with strong character and noble morals.